PENGEMBANGAN BAHAN AJAR MENYIMAK BERBASIS MEDIA AUDIO VISUAL DENGAN PEGINTEGRASIAN PENDIDIKAN KARAKTER POSITIF PESERTA DIDIK KELAS V SEKOLAH DASAR - Foni Yulia Putri; Ramalis Hakim; Desyandri; Darnis Arief; Risda Amini; Yeni Erita (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This research was motivated by the low listening ability of fifth-grade students, which was caused by the use of inappropriate teaching materials. To address this, listening materials based on audio-visual media were developed, integrating positive character education to improve students’ listening skills. The objective of this development was to produce valid, practical, and effective teaching materials. This research was research and development (R&D) utilizing the 4-D model, consisting of the stages of defining, designing, developing, and disseminating. Data on validity were obtained through RPP validation sheets and teaching materials, while practicality data were collected through lesson plan implementation, observation sheets, and teacher and student response questionnaires. Effectiveness was measured from students’ learning activities and outcomes, including character assessment and listening skills. The results showed that the developed teaching materials were very valid, practical based on teacher observations and questionnaires, and effective, with 93% of students able to listen effectively using the audiovisual media. Based on these findings, the listening materials based on audio-visual media for grade V elementary students can be declared valid, practical, and effective.